TREN PENELITIAN LITERASI DAN TEKNOLOGI PENDIDIKAN DI SEKOLAH DASAR: SEBUAH KAJIAN BIBLIOMETRIK DAN LITERATURE SISTEMATIK 2021-2025 - Fadhilah; Haryadi; Bernadus Joko Santoso (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to map and analyze the research trends on literacy and educational technology in primary education from 2021 to 2025 through a blibliometric and systematic literature review approach. Data were collected from Google Scholar and Crossref using the Publish or Perish software to facilitate the retrieval of blibliometric information. The PRISMA 2020 protocol was applied to ensure a transparent and structured review process. VOSviewer was employed to visualized the relationships among keyword and thematic clusters. The result identified three major clusters: (1) literacy and learning media, (2) analysis of technological effectiveness, and (3) implementation and cse-based learning models. The correlation among clusters indicates that literacy development serves as a conceptual basis for the application and evaluation od educational technology in primary schools. Research trends show a shift from the development of literacy-based media to the assessment of digital technology effectiveness in improving students’ learning outcomes. This study constributes to understanding the evolving landscape of digital literacy and technology integration in primary education, highlighting the importace of digital transformation for 21st-century learning skills